Resin-based Brake Pad from Rice Husk Particles: From Literature Review of Brake Pad from Agricultural Waste to the Techno-Economic Analysis - Asep Bayu Dani Nandiyanto; Dwi Fitria Al Husaeni; Risti Ragadhita; Tedi Kurniawan (Universitas Muhammadiyah Magelang, 2021)
A brake pad is the most crucial component in motorized vehicles. Many ways have been done and reported on how to prepare resin-based brake pads, but information relating to the economic analysis of resin-based brake pads on a large-scale production is still rare. This study aimed to report a literature review of brake pad production from biomass and agricultural wastes, optimal design of brake pad, and techno-economic analysis of resin-based brake pad production from rice husk. In the techno-economic analysis, we focused on engineering and economic perspectives. Engineering analysis was conducted by calculating the mass balance in the resin-brake pad production process. To support the analysis, economic parameters including gross profit margin (GPM), payback period (PBP), break-even point (BEP), cumulative net present value (CNPV), profitability index (PI), internal rate return (IRR), and return on investment (ROI) were calculated to predict the feasibility of project under ideal condition. We also calculated the techno-economic analysis for the worst cases in the project, calculating the internal problems (i.e., raw materials, sales, utility, labor, employee, fixed cost, variable cost, and production capacity) and the external issues (i.e., taxes and subsidiaries). Based on the engineering evaluation, the resin-based brake pad project is prospective. From economic evaluation, GPM, PBP, BEP, CNPV, PI, and ROI showed positive results, indicating that the project is potential for the large-scale production. This work has demonstrated the importance of the projects for further development and can be used as a reference for further production of brake pads made from agricultural waste.